POTENSI DAN DAN PENGEMBANGAN AGRIBISNIS KOPI UNTUKPENINGKATAN PENDAPATAN PETANI KOPI KABUPATEN BREBESDARI SEKTOR PERKEBUNAN - Sutarmin; Purwanto; Ivan Akmal Nur (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2019)
The agricultural sector is a leading sector in developing national development strategies. plantation subsector has the highest contribution to GDP, which is 3.46%. The GDP of the plantation subsector was obtained from superior commodities, one of which was coffee. In recent years, the stretch of coffee agribusiness in Brebes Regency has begun to appear and has increased, but the impact of increasing coffee farmers' income is still very small. Because farmers' knowledge about how to maintain coffee plants is still very low. The method of collecting data in this study is through literature studies, interviews and observations. The results of this study are (1) Salem District has the highest production yield and the most extensive land compared to 3 other Sirampog Subdistricts which have the most adequate post-harvest processing equipment. (2) The quality of human resources for coffee farmers in Brebes Regency still lacks limited knowledge. (3) Based on the value chain analysis of determinants of downstream products the coffee process is roasting and grinding. (4) Based on an analysis of internal factors shows that coffee business people in Brebes have a very strong internal position. Based on the results of the analysis of external factors showing that the Brebes Regency business actor is able to respond well to the opportunities and threats that exist and based on IE Matrix analysis, the general strategy is to develop aggressively and constructively (5) Based on the SWOT analysis, several proposed strategies are increased intensity of promotion and marketing by involving young people of productive age in each region, (2) stalls / coffee shops or cafes are established in each place (3) Empowering village youth (4) Procurement of necessary equipment, (5) Making / establishing a joint business institution (6) establishing a coffee house